Health-related quality of life in neuroendocrine neoplasia: a critical review. Issue 7 (July 2020) - White, Benjamin Easton; Druce, Maralyn R; Grozinsky-Glasberg, Simona; Srirajaskanthan, Rajaventhan; Gamper, Eva Maria; Gray, Debra; Mujica-Mota, Ruben; Ramage, John K
Abstract : Incidence of neuroendocrine neoplasia (NEN) is increasing, as is use of health-related quality of life (HRQoL) measurement in clinical trials. Following development of validated questionnaires, HRQoL is widely used to assess outcomes. This review is intended for healthcare professionals and is based on a selection of data published in the last decade. HRQoL is on par with other clinical endpoints such as performance status. Assessments in clinical trials have been particularly useful for monitoring the symptom burden of NEN, for the effects of treatments on patients' lives, and have provided new data allied to the usual clinical endpoints. QoL expressed as quality-adjusted life years (QALYs) have become the most important primary outcome to establish cost-effectiveness in health economic evaluation. From looking at clinical trials over the last 10 years, we see that the quality of HRQoL evidence reported in published studies has improved and, in general, recent studies are likely to be more methodologically robust. Assessment of HRQoL in clinical trials is likely to become a standard part of clinical practice in NEN, as in other cancers. However, clear methods for calculating the clinical meaningfulness of changes in scores are needed. Other limitations of HRQoL measurement include lack of specificity to certain symptom sets and ease of completion and administration. An international group taking a lead on developing HRQoL research specifically in NEN patients is needed to address limitations of the evidence base. In order for greater weight to be placed on HRQoL data, agreement on optimal, validated scoring systems is needed.